Identification Of Collapsible Soils In Deroua (Morocco) - Ouatiki, Kawtar; Bahi, Lahcen; Awa, Mohamed Ould; Ouadif, Latifa; Akhssas, Ahmed; Ejjaaouani, El Houcine (European Scientific Journal, ESJ, 2016)
Deroua belongs to the Berrechid plain and it is characterized generally by a flat relief, formations from the quaternary and Pliocene age and unconformably on sedimentary formations of Cretaceous and Permian Triassic on shcists from the primaries. Several anomalies were detected in the buildings and pavement structures in different cities in the territory of the Berrechid plain, such as settlement, cracking or even sudden collapses. The presence of a water table with 1500 square kilometers in area, the climatology of the region and a major urban development are factors favoring collapsing soils. Thus, we conducted a series of geotechnical tests on four samples taken from Deroua, 10 km from the city of Berrechid to identify the nature of the soils of this city in order to study their behavior in unsaturated state. The results of Atterberg limits and the oedometer test, correlated with results of previous studies and bibliographical research confirm the hypothesis of collapsible soils. Therefore, the results will help to quantify and map the collapse of soils in Deroua, in order to establish a local hazards map that can be exploited by the urban agency.